Production of canthin-6-one and stigmasterol in Eurycoma longifolia (Tongkat Ali) jack. hairy root culture transformed using Agrobacterium rhizogenes Strain A4 - Nor Hasnida Hassan,; Ling, Sui Kiong; Nazirah Abdullah,; Nur Aini Mohd Kassim, (Penerbit Universiti Kebangsaan Malaysia, 2025)
Eurycoma longifolia, commonly known as Tongkat Ali or Malaysian ginseng, contains a variety of chemical compounds, including quassinoids, canthin-6-one alkaloids, B-carboline alkaloids, squalene derivatives, and steroids. These compounds contribute to the plant’s therapeutic properties, which include anti-cancer, anti-malarial, anti-ulcer, aphrodisiac, and energy-boosting effects. Since many of these compounds are primarily extracted from the roots, overharvesting can threaten wild populations of E. longifolia. A sustainable approach to producing these chemical compounds involves cultivating hairy root cultures, which have been used successfully to produce chemical compounds in other plant species. In this study, hairy root cultures of E. longifolia were established using the Agrobacterium rhizogenes strain A4. The hairy roots were cultured in MS basal liquid medium at pH 4.9, under dark conditions on an orbital shaker (150 rpm) at 25 ± 2 °C. The production of two chemical compounds reported extracted from E. longifolia natural roots, canthin-6-one and stigmasterol, was confirmed in the extracts of the E. longifolia transformed hairy roots through High-Performance Liquid Chromatography (HPLC) and Nuclear Magnetic Resonance (NMR) spectroscopy analysis. E. longifolia hairy roots culture can be used as an alternative source for these chemical compounds.